Sentidos subjetivos identitários da prática profissional de formadoras do PROVE - Stangherlim, Roberta (2007)
This doctorate thesis emerged from questions regarding the professional development of teachers and their education. The theoretical framework is based on the areas of Psychology, specifically in the Subjectivity Theory proposed by Rey (2005, 2004, 2003, 2001), and in the area of Education, in the works of several authors that deal with the topic of Teacher Education. The research problem was outlined: What identifiable subjective meaning constitute the practice of teacher educators in continuing education? As the objective, this thesis analyzed a few subjective meaning present in the professional identities of four teacher educators at PROVE - Projeto Valorização do Educador e Melhoria da Qualidade do Ensino (Educator Valorization and Enhancement of Teaching Quality Project), with consideration to their ways of thinking, feeling, acting, and whose forms of expression - oral, written, gestural are manifested in their professional practices. Research tools were: field notes, audio recording of planning and formative meetings, and written conversation, via e-mail, with the teacher educators. It was observed that the core of the identifiable subjective meaning of the professional practice of each teacher educator is marked by singularities that converge as they are analyzed within the PROVE space. These main core correspond to the valuation of the individual, the valuation of teacher education, the valuation of the collective work, and the valuation of of written reports; and they relate to the challenge undertaken by the teacher educators that is to learn with their own professional practice and with the experience of the teacher in the process of continuing education. It is in this puzzle of differences and similarities that we find significance and subjective meaning configured in an identity that is simultaneously individual and collective. The entanglement of these subjective meaning is recognized as an identifiable mark of PROVE, which has a unique project for continuing education; there is a need to stimulate its protagonists in order to enhance the quality of teaching